New records of mosquitoes (Diptera: Culicidae) from Misiones Province, Argentina - Rossi, Gustavo Carlos (2014)
The following species represent first records for Argentina: Culex (Anoedioporpa) canaanensis Lane & Withman, Culex (Anoedioporpa) originator Gordon & Evans, Culex (Culex) declarator Dyar & Knab, Culex (Melanoconion) ribeirensis Forattini & Sallum, Culex (Microculex) neglectus Lutz, Culex (Microculex) pleuristriatus Theobald, Orthopodomyia fascipes (Coquillett) and Wyeomyia (Wyeomyia) medioalbipes Lutz. The species Anopheles (Nyssorhynchus) guarani Shannon and Ochlerotatus (Ochlerotatus) rhyacophilus (Da Costa Lima), recorded for Argentina, were recently resurrected from the synonymy of Anopheles (Nyssorhynchus) lutzii Cruz and Ochlerotatus (Ochlerotatus) scapularis (Rondani). The following species represent the first report for Misiones Province: Anopheles (Anopheles) neomaculipalpus Curry, Coquillettidia (Rhynchotaenia) fasciolata (Lynch Arribálzaga), Culex (Culex) acharistus Root, Culex (Culex) tatoi Casal & García, Culex (Culex) usquatus Dyar. With these new records the number of mosquito species for Misiones Province increases to 189 while for Argentina to 242.